Associação entre consumo alimentar, horários atípicos de trabalho e padrão de sono: um estudo com trabalhadores em turnos fixos - Silva, Graciele Cristina (2017)
Background: It is well documented in the literature that shift workers present alterations in the sleep patterns, especially the reduction of sleep time, which predisposes them to alterations in the food pattern. Objectives: To study the association between food intake, shift work and sleep time in fixed shift workers of a poultry processing agroindustry. Material and methods: A cross-sectional study was conducted with 1.215 individuals working on four fixed work schedules: 461 morning, 233 day, 146 evening and 375 night. The subjects were submitted to the following measurements: blood pressure, weight, height and waist circumference, and calculated the Body Mass Index (BMI) was calculated. The self-reported sleep duration on work and off days were calculated. Sleep time was categorized as <6: short duration and > 6 hours: adequate. Food intake was evaluated by the semiquantitative validated Food Frequency Questionnaire (FFQ) for the Brazilian adult population. The daily consumption frequency and the prevalence of inadequacy of the eight food groups proposed by the Food Pyramid Adapted for the Brazilian Population were calculated. The diet quality was also evaluated by estimating the Adapted Healthy Diet Index (IASad) for the Brazilian population. Adjusted binary logistic regression was performed for the potentially confounding variables: sex, age and schooling, to verify the association between work shifts and the inadequacy of food consumption. In addition, we performed the Poisson regression analysis with robust variance adjusted for the potentially confounding variables in order to verify the association between sleep duration and poor diet quality. Results: The data collected gave rise to two scientific papers. In the first article we found an association between the morning and night shifts and the inadequacy of the consumption of the milk and dairy products group (Adjusted Odds Ratio [AOR]: 2.49, 95% CI = 1.29-4.81, p <0.01), meat and eggs (AOR: 1.6195% CI = 1.07-2.42, p <0.05), cereals and pasta (AOR: 1.44, 95% CI = 1.01-2, P <0.05) and fruits and natural fruit juices (AOR: 2.04, 95% CI = 1.06-3.93, p <0.05). The night shift had a greater chance of inadequacy for milks and derivatives (AOR: 2.25, 95% CI = 1.19-4.25, p <0.0, meat and eggs (AOR: 1.62, 95% CI = 1.07-2.45, p <0.05) and cereals and pasta (AOR: 1.56, 95% CI = 1.09-2.24, p <0.05) compared to day shift. In the second article, the median IASad total score was 67.0 (IQR = 56.6-79.9) and 59.3% (n = 720) of the workers presented poor diet quality. Short sleep duration (mean sleep duration <6 hours) on days off and work days were associated with poor diet quality [Adjusted Prevalence Ratio (APR: 1.12, 95% CI = 1.02-1, 24, p = 0.016, APR: 1.14, 95% CI = 1.01-1.28, p = 0.028 respectively). Conclusion: Workers at atypical work schedules are more likely to exhibit inadequate consumption of various food groups. In addition, workers with short sleep duration have a higher prevalence of poor diet consumption based on IASad.